Cervical Spondylotic Myelopathy Treated with Multilevel Oblique Corpectomy. A Review of 29 Cases. - Mohamed Sawan (Egyptian Spine Association, 2012)
Study Design: We reviewed our surgical experience and results in 29 patients operated upon by multiple oblique corpectomy without fusion for cervical spondylotic myelopathy. Objective: To review the safety, efficacy and surgical experience of multiple oblique corpectomy in carefully selected 29 patients, through anterolateral corridor to the cervical spine without the need for vertebral fusion or stabilization. Methods: Between March 2007 and April 2011, 29 patients have been treated with multiple oblique corpectomy technique for cervical spondylotic myelopathy. The functional status was assessed using the modified Japanese Orthopedic Association Score preoperatively and at 1,6,12 months postoperatively. Radiological Assessment was done preoperatively with MRI, CT scan and plain radiograph, and postoperatively on the following 1,6,12 months after surgery and routinely prior to discharge. Results: Among the 29 patients (19 males and 10 females) with a mean preoperative duration of symptoms for of 11.7 months. Satisfactory significant recovery occurred in 20 patients, 5 patients had no clinical improvement and 4 patients had variable degrees of clinical deterioration. Only one patient showed an evidence of spinal instability postoperatively. Conclusion: The multiple oblique corpectomy is a safe and effective technique in removal of the anterior compressing spurs to the spinal cord. No fusion is required regardless the number of the levels. The short recovery period, few complications rate with satisfactory significant outcome make this technique a better surgical option for cervical spondylotic myelopathy in selected patients. (2012ESJ003)